Game theoretic production decisions of by-product materials critical for clean energy technologies - Indium as a case study. (15th July 2020) - Choi, Chul Hun; Kim, Sang-Phil; Lee, Seokcheon; Zhao, Fu
Abstract: Clean energy technologies represent a promising solution to the global warming challenge. However, many of them depend on some minor metals, and concerns about their rapidly increasing demand have been raised recently. Since minor metals are produced along with other materials, called base metals, they are also referred as by-product materials. With this characteristic, their production quantities rely on the production quantities of the base metals. Therefore, the production decisions for the by-product materials are not easy, and the decisions become even more complex under competitive market. This research seeks to find equilibrium production quantities of both base and by-product materials using Cournot model. Then, the model is applied to a case study of indium, which is critical for two emerging clean energy technologies, thin-film solar photovoltaic and light emitting diode lighting. The numerical analysis in the case study suggests some meaningful insights in this market, and the equilibrium production quantities are also compared with the optimal production quantity under monopoly market condition. Highlights: A Generic Cournot duopoly model for base and by-product materials is proposed. Equilibrium quantities for both materials at four distinctive cases are derived. Zinc and indium are selected as a case study to show model demonstration. A big player always produces more both materials under decoupling case. Optimal by-product quantity in all other cases is bounded by base metal quantity.